2022
DOI: 10.3389/fpubh.2022.743138
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Polypharmacy, Drug-Related Problems, and Potentially Inappropriate Medications in Geriatric Patients and Its Implications for Bulgaria—Narrative Review and Meta-Analysis

Abstract: ObjectivePolypharmacy and inappropriate prescribing are overlooked issues in Bulgaria. We aimed at collecting and analyzing global literature on the most prevalent risk factors and investigating what they could reveal about current practice.Materials and MethodsA systematic narrative review and meta-analysis was conducted on the topic, investigating the prevalence of polypharmacy, odds of potentially inappropriate medications (PIMs) due to polypharmacy, and the likelihood of developing a drug-related problem (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Previous study performed a meta-analysis of the reported risks for PIPs and related risk for Bulgaria ( 34 ). It calculated that 244,227 people are exposed to risk for PIP in the population above 65 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study performed a meta-analysis of the reported risks for PIPs and related risk for Bulgaria ( 34 ). It calculated that 244,227 people are exposed to risk for PIP in the population above 65 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…(16 patients). In geriatrics, polypharmacy can lead to DRPs [4], hospitalization and nonadherence to medications [15].…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The most prevalent form of diabetes in older people is type 2 diabetes mellitus (T2DM). The geriatric population is susceptible to many co-morbidities and complications of DM that can affect morbidity and mortality [3] making it possible to experience polypharmacy associated with drug-related problems (DRPs) [4]. Medicine interactions, polypharmacy, and incorrect drug prescriptions in the elderly can all have a negative impact on their quality of life, necessitating extra care [5].…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt, there is an increasing incidence of cancer (6) . Polypharmacy is a major issue for cancer patients, especially in the elderly and it is a key risk of occurrence of DRPs (7) . Cancer treatment is complex and could result in many DRPs such as adverse reactions, medication errors, DDIs, and nonadherence which may cause drug-related morbidity and mortality (8) , that's why detecting and resolving them is critical to achieving the optimum therapeutic outcomes and minimize cost spent for emergency department visits, hospital admissions and additional visits that could be needed as a result of DRPs (9) .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that including hospital pharmacists in multidisciplinary teams improves the detection and resolution of DRPs (11) . There is a need for clinical pharmacist intervention that could minimize DRPs and improve QoL (6,7) .…”
Section: Introductionmentioning
confidence: 99%